Proteome-Wide Analysis of Lysine 2-Hydroxyisobutyrylated Proteins in Fusarium oxysporum - Qian, Hengwei; Wang, Lulu; Ma, Xianliang; Yi, Xingling; Wang, Baoshan; Liang, Wenxing (Frontiers in Microbiology, 2021)
Protein lysine 2-hydroxyisobutyrylation (Khib), a new type of post-translational modification, occurs in histones and non-histone proteins and plays an important role in almost all aspects of both eukaryotic and prokaryotic living cells. Fusarium oxysporum, a soil-borne fungal pathogen, can cause disease in more than 150 plants. However, little is currently known about the functions of Khib in this plant pathogenic fungus. Here, we report a systematic analysis of 2-hydroxyisobutyrylated proteins in F. oxysporum. In this study, 3782 Khib sites in 1299 proteins were identified in F. oxysporum. The bioinformatics analysis showed that 2-hydroxyisobutyrylated proteins are involved in different biological processes and functions and are located in diverse subcellular localizations. The enrichment analysis revealed that Khib participates in a variety of pathways, including the ribosome, oxidative phosphorylation and proteasome pathways. The protein interaction network analysis showed that 2-hydroxyisobutyrylated protein complexes are involved in diverse interactions. Notably, six 2-hydroxyisobutyrylated proteins, including three kinds of protein kinases, were involved in the virulence or conidiation of F. oxysporum, suggesting that lysine 2-hydroxyisobutyrylation plays regulatory roles in pathogenesis. Moreover, our study shows that there are different Khib levels of F. oxysporum in conidial and mycelial stages. These findings provide evidence of Khib in F. oxysporum, an important filamentous plant pathogenic fungus, and serve as a resource for further exploration of the potential functions of Khib in Fusarium species and other filamentous pathogenic fungi.